Knowledge and attitudes of academicians towards organ donation: a concept paper / Liatul Izian Ali Husin ...[et al.] - Ali Husin, Liatul Izian; Mohamad Mozie, Noorizan; Ghazali, Norfazlina Ghazali; Azizam, Nor Azmaniza (Faculty of Business and Management UiTM Shah Alam, 2020)
The purpose of this paper is to examine the contributing factors towards the intention to become an organ donor. The literature review is on the main issue about the awareness of public about organ donation. In Malaysia only 420,601 pledgers of organ donation which is equivalent to 1.3 percent of the total population of Malaysia. This figure is not sufficient to meet the demand from patients in the organ waiting list. Literature reported that the level of awareness in Malaysia is still low. Low organ donation rates have been linked to a lack of public awareness and knowledge about organ donation. In order to get a better insight of what factors that may contribute to the intention of a person to become an organ donor, this paper, based on the past literature propose two factors: Knowledge and attitude as the predictor variables towards intention. The study intends to collect data from the academician in the Universiti Teknologi MARA, Selangor. The outcome of this research can offer a better understanding towards the intention to become an organ donor. It also provide a better insight to the public health agency to disseminate information to increase the awareness and knowledge about organ donation.